Ciclos de formação e desenvolvimento humano a proposta oficial e sua efetivação em duas escolas da rede municipal de ensino de Goiânia - Oliveira, Nilza Maria de (2005)
The present study had for objective the investigation of the organized education system for Cycles of Formation and Human Development in two schools of the Municipal Net of Goiânia, verifying the correlation between the teaching conception and learning assumed by the teachers and the activities that accomplish at classroom. The basic supposition was that the organized education system for cycles, when introducing changes in the teachers' pedagogic practices resulted in the students' better learning with the implication of the teachers' work. In that way, the research could verify the teaching conception and learning of the same ones and as the proposal of the Municipal General office of Education was executed, for that the following objectives were proposed: the study of the learning theories that they base the proposal of the system of cycles in the documents of the municipal net of teaching of Goiânia; b) the verification of the teachers' conceptions on the teaching process and learning in relation to the official proposal of the cycles; c) the correlation among those conceptions and the teaching activities and learning that the teachers accomplish at room, in way to verify what was prioritized by the teachers in the teaching activities and learning. The analysis of the dates collected through the field observation, of the interviews and of the official documents it made possible the comparison between the proposal and the teachers' practice. To reach the objectives, she proceeded a historical analysis concerning the attempts of differentation of the education systems in national and international level leaving of the English experience in the decade of 1950, came also the report of the cycles in Brazil and the different authors' influences in the proposal of the Municipal Net of Teaching of Goiânia. The research was driven in a qualitative approach, with the use of the analysis of content of the official documents of the Municipal General office of Education, of the interviews accomplished with the teachers and of the registrations of observation of the school and of the classroom. It was possible to notice that the Municipal Net of Teaching executed changes in the Projeto Escola Para o Século XXI culminating in the proposal of the administration 2001/2004 being rendered the automatic progression, however, the changes in the teachers' practices were not executed in agreement with the expected by the proposal.